Rapid Convergence of Approximate Solutions for Fractional Differential Equations - Xiran Wu; Junyan Bao; Yufeng Sun (Journal of Function Spaces)
In this paper, we develop a generalized quasilinearization technique for a class of Caputo’s fractional differential equations when the forcing function is the sum of hyperconvex and hyperconcave functions of order m (m≥0), and we obtain the convergence of the sequences of approximate solutions by establishing the convergence of order k (k≥2).